Which dietary components modulate longitudinal growth?. Issue 3 (May 2017) - Gat-Yablonski, Galia; Yackobovitch-Gavan, Michal; Phillip, Moshe
Abstract : Purpose of review: Linear growth in children is sensitive to nutritional status; the growth of the human skeleton requires many different nutritional factors for energy and building blocks: proteins, lipids, carbohydrates and micronutrients. However, what are the specific nutritional factors that are required for proper growth and what is the composition that will be most beneficial is still not known. Recent findings: Recent findings indicate that macro and micronutrients are required as building blocks and as cofactors for important enzymes. In addition, they stimulate linear growth by acting as regulatory factors and also affect gut microbiome. Some interesting studies regarding the effect of proteins and amino acids are presented. Summary: Most studies investigated the effect of replacing a single micronutrient that was deficient; however, in real life, deficiency of one nutritional element is commonly associated with other deficiencies. Therefore, it is a reasonable clinical approach, both in developing and developed countries, to use a mixture of both macro and micronutrients to support growth. How much of each of the components and what is the best composition are still open questions that require more research.